CORRELATION OF GADGETS ADDICTION WITH SLEEP QUALITY IN 4th – 6th GRADE STUDENTS AT SDN 01 SRIGADING LAWANG IN 2019 - Niro, Agustin J Nanda De; Pawitra, Annisa; Faizah, Novia Nurul; Putra, Rendra Dwi; Arfiputri, Veikha Fakhriya; Sihombing, Renata Violia; Rachmi, Shabrina Noor; Nuswantoro, Djohar; Martha, Ledy (Universitas Airlangga, 2020)
The use of digital technology has increased rapidly. In Indonesia, gadget use by children has become very high and requires special attention. Many effects may occur due to gadget use, one of which is sleep quality disturbance. This study aims to analyze the correlation between gadget addiction and sleep quality in children grades 4-6 SDN 01 Srigading Lawang. This research is an analytic observational study with a cross-sectional design in a population of 4-6th graders of SDN 01 Srigading Lawang. A total of 126 students over 130 students were included. Data were collected using two questionnaires, which are Smartphone Addiction Scale and The Pittsburgh Sleep Quality Index, and tested using RxC Contingency. Gadget addiction has a significant correlation with sleep quality with a weak correlation. Children with mild levels of addiction to gadgets had a potential of 2,013 times to have good sleep quality, compared to children with moderate levels of addiction. In contrast, children with severe levels of addiction to gadgets were at risk 12.04-fold to have poor sleep quality compared to the mild level of addiction. There is a significant correlation with a weak correlation between gadget addiction and sleep quality in children grades 4-6 SDN 01 Srigading Lawang.